Rancang Bangun Aplikasi E-Commerce Menggunakan Model Scrum (Studi Kasus : Webake Bakery & Cookies) - Sulistyo; Maulana Ardhiansyah (CV. Multi Kreasi Media, 2023)
In the era of advanced technology like now, primary needs such as clothing and food can easily be ordered through a website or application with a smart phone or with a computer. Almost all food can be ordered through social media applications, online motorcycle taxis and restaurant-owned applications. Even kitchen ingredients can be purchased in e-commerce applications. No cakes and breads that can be ordered with these applications. Therefore, this research will create a website-based product ordering information system so that it can make it easier for customers to order products. For the system development method, the author uses the Scrum method. For programming language using PHP and database using MySQL. This system makes it easy for customexrs to order products without having to order via direct messages, sellers can manage orders easily and easily.